2014
DOI: 10.1109/jsac.2014.2332119
|View full text |Cite
|
Sign up to set email alerts
|

Demand Side Management in Smart Grids Using a Repeated Game Framework

Abstract: Demand side management (DSM) is a key solution for reducing the peak-time power consumption in smart grids. To provide incentives for consumers to shift their consumption to off-peak times, the utility company charges consumers differential pricing for using power at different times of the day. Consumers take into account these differential prices when deciding when and how much power to consume daily. Importantly, while consumers enjoy lower billing costs when shifting their power usage to off-peak times, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Recent DSM studies [2][3][4][5][6][7][8], have presented some techniques for appliance energy consumption scheduling, peak demand reduction (PDR), and Peak-to-Average-Ratio (PAR) demand reduction with some level of consumer preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Recent DSM studies [2][3][4][5][6][7][8], have presented some techniques for appliance energy consumption scheduling, peak demand reduction (PDR), and Peak-to-Average-Ratio (PAR) demand reduction with some level of consumer preferences.…”
Section: Introductionmentioning
confidence: 99%
“…The common goal of these studies is to find optimal strategies for consumers or suppliers by considering the impact of pricing mechanisms [3,12,[17][18][19][20][21][22][23][24]. In [10], the authors suggested a DSM strategy that uses a day-ahead load shifting technique to overcome both peak load demand problems.…”
Section: Introductionmentioning
confidence: 99%
“…In [10], the authors suggested a DSM strategy that uses a day-ahead load shifting technique to overcome both peak load demand problems. The work of Song [24] proposed an optimal critical peak pricing scheme for DSM by considering the interactions of consumers where there is a single utility company. In this work, a repeated game framework for nonstationary DSM was proposed to minimize the long-term total cost and discomfort cost of consumers.…”
Section: Introductionmentioning
confidence: 99%
“…DSM has been proved useful for the residential sector, commercial sector, and industry sector [13]- [16]. It has been realized in practice in recent years, supporting many appliances, such as space heating [17], water heaters [18], and electric vehicles [19].…”
Section: Introductionmentioning
confidence: 99%
“…In [14]- [16], the DR aggregators were mentioned as the intermediary, but the revenue of it was not considered. In [13], the electricity bill of consumers was emphasized, but the associated discomfort level was not taken into account. In [12] and [20], only conventional generation was considered.…”
Section: Introductionmentioning
confidence: 99%